The Dominance of Blended Emotions: A Qualitative Study of Elementary Teachers’ Emotions Related to Mathematics Teaching - Cross Francis, Dionne Indera; Hong, Ji; Liu, Jinqing; Eker, Ayfer; Lloyd, Kemol; Bharaj, Pavneet Kaur; Jeon, MiHyun (Frontiers in Psychology, 2020)
Examining the nature of teachers’ emotions and how they are managed and regulated in the act of teaching is crucial to assess the quality of teacher’s instructions. Despite the essential role emotions play in teachers’ lives and instruction, research on teachers’ emotions has not paid much attention on teachers’ state emotions in the context of daily teaching. Significant portion of literature has described teachers’ emotions by foregrounding trait emotions through deductive methodological approaches. This paper explored elementary teachers’ state and trait emotions while preparing for teaching and during teaching, reasons that underlie these emotions, and the relationship between their emotions and the quality of their mathematics instruction. Participants were seven elementary teachers working in the U.S. who participated in Holistic Individualized Coaching (HIC) professional development that consisted of 5 cycles of coaching over an year. For each coaching cycle pre-coaching conversation and post-coaching conversation data were collected regarding state emotions teachers felt in anticipation of teaching and during teaching retrospectively. Also, teachers responded adapted Teaching Emotion Scale (TES) that was aimed to measure trait emotions. In order to compare teachers’ emotions with instructional quality, coaching session were video recorded and analyzed to determine the quality of instruction. Findings of this study showed that teachers reported 6 categories of emotions (positive, negative, neutral, mixed-positive, mixed-negative, and mixed-complex), and often in non-typical ways (e.g., “not nervous”, “anxious but in a positive way”), and mixed emotions were the most dominant category. Also, teachers had more positive emotions anticipating teaching, than actually teaching the lesson, and there was no noticeable change of emotions across the 5 coaching cycles. The reason teachers felt mixed emotions reflected complex and context-specific nature of teaching, which was not articulated in the literature. There were no clear relationships between emotional experiences and instructional quality. This study allowed participants to freely describe their authentic, complex, overlapping, and ambiguous emotions in the context of active teaching, which contributes opening up the possibilities of diversifying teacher emotion research and shows the significance and usefulness of understanding teachers’ state emotions